Strategies to Raise Cultural Awareness and Create Multicultural Materials and Activities in the Language Classroom - Solano Campos, Ana Tristana (2009)
Nowadays, language teaching professionals face the challenge to incorporate culture in their instructional practice. This paper helps them explore their cultural beliefs and develop skills to evaluate and create cultural materials and activities in the language classroom.